The evolving landscape of REDD+ projects - Sills, E.; Madeira, E.R.; Sunderlin, William D.; Wertz-Kanounnikoff, Shiela (Center for International Forestry Research, 2009)
The landscape of REDD+ projects varies significantly across countries, reflecting differences in land tenure systems, drivers of deforestation, recent experience with conservation programmes and governance capacity. Indonesia appears to have the most REDD+ projects in the pipeline, with a substantial portion seeking to establish additionality, permanence and a legal claim to carbon by obtaining concessions. In Brazil, two common strategies are to initially seek carbon credits from afforestation or reforestation and to develop local-level payments for environmental services (PES) schemes. Third-party certification standards and international environmental organisations are major influences on project development.